Cloud Computing : A Practical Approach - Velte, Anthony T.; Velte, Toby J.; Elsenpeter, Robert (New York McGraw-Hill, 2010)
Contents: cloud computing basics; your organization and cloud computing; cloud computing with the Titans; the business case for going to the cloud; hardware and infrsdtructure; accessing the cloud;...
Includes index
Keywords: Công nghệ thông tin